ESRA19-0598 Ultrasound guided superior trunk percutaneous neuromodulation to treat contralateral acute on chronic shoulder pain after shoulder surgery under GA and interscalene block. (30th August 2019) - Thottungal, A; Parameswaran, V
Abstract : Background and aims: Acute on chronic shoulder pain in the contralateral shoulder after positioning for shoulder surgery can be very severe and difficult to treat especially if patient has had interscalene block on the operative side already. This is a case report of about using superior trunk percutaneous neuromodulation and block using ultra low volume for the contralateral shoulder pain management. Methods: A 54 year old male with history of bilateral shoulder pain had left shoulder surgery in the right lateral position. He had interscalene block using 20 ml of 0.5% levobupivaciane on the left side. His past medical history included obstructive sleep apnoea, high opioid use, high BMI, COPD and hypertension. In the recovery area patient complained of severe pain (10/10) in the contralateral shoulder. He had 20 mg oromorph which made him drowsy. Patient still complained of pain 9/10. He had an ultrasound guided superior trunk percutaneous neuromodulation using 0.2 mA, 2Hz, 1 ms for 5 minutes and block performed using 1.5 ml levobupivacine and 3.8 mg preservative free dexamethasone. Results: Immediately he had full range of movement in his shoulder. Pain score went down to 0/10 after 7 minutes. Follow up showed that block lasted for 36 hours. He didn't need any opioids. After a week with physiotherapy he continued having the pain relief. Conclusions: Percutaneous temporary neuromodulation is a modality used to treat chronic pain conditions. Recently neuromodulatory techniques has been used for acute pain management as well. This case demonstrates how this technique can be used effectively for shoulder pain management in a patient who needed bilateral shoulder blocks.